Cost-effectiveness analysis of deep brain stimulation for the treatment of alcohol use disorder and alcoholic liver disease - Oluwatofunmi A. Abiola; Collin M. Lehmann; Khaled Moussawi; Hawre Jalal (Brain Stimulation)
Background: Alcohol use disorder (AUD) is a major public health concern and cause of mortality and morbidity. Alcohol-associated liver disease (ALD) is a debilitating complication of AUD, mitigated by abstinence from alcohol use. Deep brain stimulation (DBS) is emerging as a potential treatment for AUD. However, its cost-effectiveness compared to the standard medical treatment is unclear. Objective: To estimate the cost-effectiveness of DBS compared to medical management for patients with AUD and ALD. Methods: We utilized a decision analytic model based on published literature to conduct a cost-effectiveness analysis of costs and health outcomes for DBS and medical management in patients with AUD and ALD. We also carried out a threshold analysis to determine the probability of success necessary for DBS to be cost-effective. Costs were measured in 2024 US dollars and effectiveness in quality-adjusted life years (QALYs). We used a time horizon of 1–2 years and adopted a societal perspective. Results: Our results show that for AUD patients in general, DBS is not cost-effective at any DBS success rate. However, for advanced ALD patients, defined as fibrosis stage 3 or beyond DBS becomes cost-effective. For these patients, DBS is cost-effective over a two-year period at a $100,000 willingness-to-pay threshold at DBS success rates greater than 53 %. For advanced decompensated ALD patients, DBS is cost-effective over a one-year period at DBS success rate greater than 35 %. Conclusion: Should it prove efficacious, DBS may be cost-effective for patients with AUD and ALD. Thus, future randomized controlled trials to evaluate its efficacy are warranted.